Knowledge, attitude and practice regarding menstrual hygiene among adolescent girls in a rural private school - Bhatt, Miti Dwijen; Kadam, Deepali Mohan (International Journal Of Community Medicine And Public Health, 2019)
Background: Being a developing country, India is faced with many health problems which can be averted by education and implementation of basic guidelines. Menstrual hygiene is one such topics which is rarely brought to attention but forms an integral part of a women’s life. This topic has been neglected not only in rural areas but in the poor socioeconomic corners of metropolitan cities. This ignorance has taken a great toll on the quality of life of women. Poor hygiene predisposes them to reproductive tract infections which may lead to increased incidence of infertility and mortality. Misconceptions regarding this have also prevented women to seek out professional help. Keeping this in mind the study was undertaken to spread awareness and eliminate the taboo this topic is regarded with. Methods: A cross sectional study was conducted amongst adolescent girls in a private school located in Angaon village, Bhiwandi Taluka, Mumbai. A self-administered questionnaire was given to the adolescent girls to assess their knowledge, attitude and practices regarding menstrual cycle. Percentages were used for statistical analysis. Results: 83 girls (96.51%) were aware of menstrual cycle. 49 (56.98%) girls perceived that menstrual blood is dirty. 72 (83.72%) knew that it is a physiological process. 85 (98.84%) were also aware about menstrual hygiene. 85 (98.4%) felt that girls should be addressed regarding menstrual cycle, hygiene before achieving menarche. 50 (58.14%) girls followed restrictions during menstruation. Conclusions: The findings of the present study emphasize the need to address physiology about menstrual cycle as well as the myths and misconceptions associated with it.